Up to date evidence about the suitability of filamentous fungi as a feed source for broilers - Ringseis, Robert; Eder, Klaus; Justus Liebig University Giessen (My University, 2025)
Biomass from cultivated edible mushrooms can be sustainably produced using residual lignocellulosic sidestreams from agriindustrial and wood processing and is a rich source of a variety of bioactive compounds. While edible mushrooms have a long history as a tasty and healthy food for humans,the potential of ,ushrooms (fungal fruiting bodies), fungal mycelia and by-products from mushroom production (stem residues, spent mushroom substrate) as feed component for poultry is less acknowledged. Based on this, the present review aims to describe the role of filamentous fungi in circular feed production, characterise the nutritional value of fungal biomass, and provide up to date evidence about the efficacy of feeding fungal biomass on performance of broilers. Feeding studies with healthy and parasite-infected Broilers using fungal fruiting bodies, mycelia, stem residues or spent mushroom substrate nearly equally showed either positive or neutral effects on growth performance, whereas impairments of performance and carcass parameters were not reported. Improvements of broiler performance in response to feeding fungal biomass were at least partially associated with a beneficial modulation of the gut microbiota community structure – effects that are most likely attributed to the presence of fermentable polysaccharides and phenolic compounds with prebiotic and selective antimicrobial activities,respectively. Based on the evidence from literature presented in this review, the inclusion of fungal biomass, particularly inexpensive by-products from mushroom production like stem residues and spent mushroom substrate, in broiler diets can be recommended, because even if no growth-promoting effects are induced the partial replacement of less sustainably produced feed components by fungal biomass improves the environmental impact of broiler production. Considering that the number of broiler studies showing either positive or neutral effects of fungal biomass on growth performance is broadly balanced and divergent study outcomes are reported even for biomass from the same fungal species, future studies are necessary to identify the specific requirements of fungal biomass responsible for promoting broiler performance.